Sustainable phosphate management Environmental and Social life cycle assessment of phosphate mining in Tunisia - Issaoui, Roukaya (KIT Scientific Publishing, 2023)
Phosphorus is a crucial element in agriculture to feed the fast-growing global population. Its sustainable supply has ecological, social and human dimensions and it is classified as critical to European industries. On the other side, phosphate can also be critical for the producing countries as phosphate mining contributes to their national economies. This work investigates implications of environmental and social impacts and the resource governance to mitigate global phosphate criticality.